Preoperative Breast Immune Prognostic Index as Prognostic Factor Predicts the Clinical Outcomes of Breast Cancer Patients Receiving Neoadjuvant Chemotherapy - Chen, Li; Kong, Xiangyi; Huang, Shaolong; Su, Zhaohui; Zhu, Mengliu; Fang, Yi; Zhang, Lin; Li, Xingrui; Wang, Jing (Frontiers in Immunology, 2022)
Objective: This study aims to investigate the potential prognostic significance of breast immune prognostic index (BIPI) in breast cancer patients who received neoadjuvant chemotherapy (NACT). Methods: The optimal cut-off value was calculated through receiver operating characteristic curve (ROC). The correlations between BIPI and clinicopathologic characteristics were determined by Chi-square test or Fisher’s exact test. The Kaplan-Meier method was used to estimate the survival probability, and the Log-rank test was used to analyze the differences in the survival probability among patients. The univariate and multivariate Cox proportional hazards regression model was used to screen the independent prognostic factors. A prognostic nomogram for disease-free survival (DFS) and overall survival (OS) was built on the basis of the multivariate analyses. Furthermore, the calibration curve and decision curve analysis (DCA) were used to assess the predictive performance of the nomogram. Results: All enrolled patients were split into three subgroups based on BIPI score. The mean DFS and OS of the BIPI score 0 group and BIPI score 1 group was significantly longer than that of the BIPI score 2 group (42.02 vs 38.61 vs 26.01 months, 77.61 vs 71.83 vs 53.15 months; P＜0.05). Univariate and multivariate analyses indicated that BIPI was an independent prognostic factor for patients’ DFS and OS (DFS, hazard ratio (HR): 6.720, 95% confidence interval (CI): 1.629-27.717; OS, HR: 8.006, 95%CI: 1.638-39.119). A nomogram with a C-index of 0.873 (95%CI: 0.779-0.966) and 0.801 (95%CI: 0.702-0.901) had a favorable performance for predicting DFS and OS survival rate for clinical use by combining immune scores with other clinical features. The calibration curves at 1-, 3-, 5-year survival suggested a good consistency between the predicted and the actual DFS and OS probability. The DCA demonstrated that the constructed nomogram had better clinical predictive usefulness than only BIPI in predictive clinical applications of 5-year DFS and OS prognostic assessments. Conclusions: The patients with low BIPI score has better prognoses and longer DFS and OS. Furthermore, the BIPI-based nomogram may serve as a convenient prognostic tool for breast cancer and help clinical decision-making.